Isolation of plastids and mitochondria from Chromera velia - Sharaf, Abdoallah; Füssy, Zoltán; Tomčala, Aleš; Richtová, Jitka; Oborník, Miroslav (Planta, 2019)
We present an easy and effective procedure to purify plastids and mitochondria from Chromera velia. Our method enables downstream analyses of protein and metabolite content of the organelles. Chromerids are alveolate algae that are the closest known phototrophic relatives to apicomplexan parasites such as Plasmodium or Toxoplasma. While genomic and transcriptomic resources for chromerids are in place, tools and experimental conditions for proteomic studies have not been developed yet. Here we describe a rapid and efficient protocol for simultaneous isolation of plastids and mitochondria from the chromerid alga Chromera velia. This procedure involves enzymatic treatment and breakage of cells, followed by differential centrifugation. While plastids sediment in the first centrifugation step, mitochondria remain in the supernatant. Subsequently, plastids can be purified from the crude pellet by centrifugation on a discontinuous 60%/70% sucrose density gradient, while mitochondria can be obtained by centrifugation on a discontinuous 33%/80% Percoll density gradient. Isolated plastids are autofluorescent, and their multi-membrane structure was confirmed by transmission electron microscopy. Fluorescent optical microscopy was used to identify isolated mitochondria stained with MitoTrackerTM green, while their intactness and membrane potential were confirmed by staining with MitoTrackerTM orange CMTMRos. Total proteins were extracted from isolated organellar fractions, and the purity of isolated organelles was confirmed using immunoblotting. Antibodies against the beta subunit of the mitochondrial ATP synthase and the plastid protochlorophyllide oxidoreductase did not cross-react on immunoblots, suggesting that each organellar fraction is free of the residues of the other. The presented protocol represents an essential step for further proteomic, organellar, and cell biological studies of C. velia and can be employed, with minor optimizations, in other thick-walled unicellular algae.
Keywords: plastidy; Microalgae; Isolation; Alveolata; Mitochondrion; Mitochondria; Plastid; mikrořasy; Chromerids; Plastids; mitochondrie